A Comparison of the Effects of Lidocaine or Procaine containing St. Thomas No. 2 Cardioplegia Solution on Post-operative Renal Function - Balachandran, Vipin; Zhou, Xinrui; Huang, Linna; Tee, Rebecca; Paul, Priyanka; Dittmer, John; Bayly, Marcus; Armarego, Sarah; Singh, Taranpreet; Seah, Peng; et al. (Cardiology and Cardiovascular Medicine, 2020)
Acute kidney injury (AKI) is one of the most common complications after cardiac surgery and is thought to result as a complex interplay between peri-operative factors. The effects of cardioplegia on renal function have not been well defined. We compared the effects of St. Thomas No. 2 cardioplegia solution modified with lidocaine or procaine and found no statistically significant difference in between the two groups. We carried out further multivariate testing adjusting for diabetes and found no statistically significant changes in renal function between the two groups.